Inclusion for all in VET? A comparative overview of policies and state of research about migration, integration and inclusion in Germany, Austria and Switzerland - Kimmelmann, Nicole; Miesera, Susanne; Moser, Daniela; Pool Maag, Silvia (MIGRATION AND INCLUSION IN WORK LIFE – THE ROLE OF VET, 2022)
Purpose: Migration and Inclusion are highly interconnected emergent issues in most European countries, addressing learners’ diversity. International conventions, such as the declaration of inclusion by the Agenda 2030 (UNESCO) request the availability of high-quality VET for all individuals, regardless of personal attributes such as ethnical background or special needs, and with special respect to the worldwide refugees. In contrast, immigrants and learners with special needs are still risk groups of discrimination and lacking equal access to VET in most countries. National policies, measures and research activities are quite various, independent and not interconnected, although international comparative research has a long tradition in VET. The paper connects to this gap and delivers a comparative comprehensive overview of the educational policies connected with migration and inclusion in Germany, Austria and Switzerland to identify similarities/differences in dealing with migration and inclusion. Results are to be dused to identify success factors and to address research gaps for a further common VET policy and research with respect to these issues. b) Approach: Categories of the analytical comparison are the understanding of integration/inclusion, structures and formats to address immigrants and learners with special needs on institutional level in VET, state of research in both areas on the micro-, macro- and meso-levels, as well as indicators of success in dealing with migration and inclusion in the three countries. c) Findings: The comparative analysis demonstrate the use of terminology as a dynamic and different process in every country, with consequences for categories of allocation to VET and training structures/formats. The high significance of dual training in the three countries and the strong market orientation in the transition from school to work are evident. The combination of language support, vocational orientation, flexible and barrier free forms of training (e.g. first place then train) as well as support services alongside training are shown to be beneficial in all countries. Discriminatory and disadvantageous processes within the VET system are responded by increased mobility (change of training formats, post-qualification, individual access rights) and flexibility (partial qualification, different educational qualifications, training duration). d) Key message: Based on the results the authors suggest a stronger international comparative analysis focusing the wider interpretation of inclusion by using the term and perspective of diversity and diversity management. The underlying intersectionality might help to overcome stereotypes and deficit-orientation towards the extremely diverse target groups.<br
Keywords: Comparative Analysis; Interconnection between Migration; Inclusion and Diversity; Germany; Austria; Switzerland; Inklusion